Preparation and in vitro Evaluation of Polylactic Acid Microspheres Containing Lamotrigine - SAINI, T.R.; DRABU, SUSHMA; JALEES AHMAD, FARHAN; KHATRI, SMRITI (Asian Journal of Chemistry, 2010)
The aim of this study was to prepare and evaluate polylactic acid microspheres containing lamotrigine. Microspheres were prepared by solvent evaporation method using methylene chloride solvent. The influence of formulation factors (stirring speed, polymer: drug ratio, stabilizer: drug ratio) on particle size, encapsulation efficiency and in vitro release characteristics of the microspheres were investigated. The yields of preparation and the encapsulation efficiencies were high for all formulations. Particle size changed by changing the polymer:drug ratio or the stirring speed of the system.